Oracle mobile application framework developer guide : build multiplatform enterprise mobile apps - Bors, Luc (McGraw-Hill Education, 2015)
"Master Oracle Mobile Application Framework In Oracle Mobile Application Framework Developer Guide, Oracle ACE Luc Bors explains how to use this powerful tool to create multiplatform mobile apps based on a single code base. Detailed examples and ready-to-use code are provided throughout the book. A complete, step-by-step sample application highlights the robust functionality of Oracle Mobile Application Framework, including data visualization, UX patterns, geographical maps, push notifications, and more. Take full advantage of the visual and declarative development features of Oracle Mobile Application Framework with help from this Oracle Press resource. Configure your IDE for Android and Apple iOS application development Build AMX pages and task flows for mobile applications Work with the binding layer and data controls Create application features and configure access to them in the springboard and navigation bar Call web services using a data control and create an on-device database Implement device interaction services Debug, test, and secure Oracle Mobile Application Framework applications Build an interactive sample app that maximizes Oracle Mobile Application Framework capabilities"--